The 4I Transformation Model for Achieving World-Class Education through Leadership, Quality, and Inclusivity at SMP President Cikarang - Agus, Hasan Basri; Latif, Muhktar; Syahran, M.; Wiratih, Hernawati Wibawati Retno; Syahrasaddin, Syahrasaddin (Jurnal Ragam Pengabdian, 2026)
This study develops an integrative mechanism of educational transformation toward World-Class Education through visionary leadership, quality management, standardization, and the internalization of multicultural-inclusive values at President Junior High School, Cikarang. It employed an integrative qualitative case-study design through secondary analysis of three mini-research reports produced from the same intensive field visit. The analytical corpus comprised three complete reports, 28 initial indicators, observation-documentation matrices, and three conceptual models. Data were analyzed through indicator consolidation, cross-case matrices, searches for convergence and tension, inter-report triangulation, and pattern synthesis. The findings show that a world-class orientation does not operate as a stand-alone internationalization program. Visionary leadership provides direction and change energy; quality management and standardization institutionalize the vision through governance, curriculum, teacher competence, technology, data, and evaluation; while multicultural-inclusive values and world citizenship provide ethical substance, safety, and equitable participation. The synthesis produces the 4I-WCE Model: inspiration, institutionalization, internalization, and impact, supported by data- and stakeholder-based feedback. The model demonstrates that World-Class Education should balance academic-global quality with character, well-being, inclusion, and social responsibility. The study is limited by the brief field duration, the absence of verbatim transcripts in the secondary corpus, and the lack of longitudinal evidence.